مقترحات اتفاقیة بازل 3 للوقایة من الأزمات البنكیة لتعزیز استقرار النظام المالي في ظل الإطار العولمي الجدید - بـهوري نبیل (Finance and Business Economies Review, 2018)
The purpose of this article is to highlight the role of the Basel 3 proposals for the prevention of banking crises to improve the stability of the financial system in the light of financial globalization, where the banking system is one of the most the most important financial parts of the system, and the stability of the system is linked to the stability of the banking system, and among the reasons that led The instability of the banking system is the globalization of financial markets and the emergence of many financial innovations. The growing trend towards the application of globalization and financial liberalization and the associated integration of markets and the free flow of capital to make the issue of financial stability stand on the list of countries' concerns, and undergoing total banking supervision is of great importance, including the Basel Convention 3, by experiences with the application of the policy of financial liberalization The banker confirmed to the monetary authorities and the supervisory bodies of the financial system that this policy should be combined with effective supervision of the banking system to avoid financial crises.